HPLC-DAD method for simultaneous determination of natural polyphenols - Vanya Dimcheva; Nikolay Kaloyanov; Maria Karsheva; Milena Funeva-Peycheva; Nadezhda Stoilova (Open Journal of Analytical and Bioanalytical Chemistry - Peertechz Publications, 2019)
A simple and reliable high-performance liquid chromatography with diode-array detection (HPLC-DAD) method was developed for simultaneous determination of 9 natural substances common in plants: three major catechins ((-) - epicatechin gallate, (-) - catechin, (-) - epigallocatechin), four major flavonoids (rutin, quercetin, myricetin, kaempferol), gallic and vanillic acid. The optimized method was carried out for 40 minutes with detection wavelengths of 278 and 368 nm, gradient elution system on a C18 reversed-phase column. The developed system was evaluated for several validation characteristics, as system suitability, specificity, linearity, limit of detections (LODs) and limit of quantifications (LOQs). The newly established HPLC method was proved to be specific, sensitive, linear and precise. The received results showed good chromatographic separation and assumed that the described method was validated. The HPLC-DAD method can be a useful tool for the quantitative and qualitative evaluation of the selected polyphenol compounds and can be improved in the future for the examination of the polyphenols of interests in individual herbal infusions.